Assessing The Role of Financial Development in Macroeconomic Stability: A Time-series Analysis of Pakistan - Munir, Nasir; Kakar, Mehmood (Asian Journal of Applied Economics, 2023)
This study aims to investigate the relationship between financial sector advancement and macroeconomic stability in Pakistan over the period of 1980–2021. By analyzing data from the State Bank of Pakistan, the study focuses on the causal relationship between various factors of financial development in Pakistan and the stability of macroeconomic indicators. The study utilizes a balance of payment to GDP as the dependent variable, while the explanatory variables include M2 to GDP, bank claim on private sector ratio to GDP, equity market capitalization to GDP, national saving to GDP, and inflation. The study applies statistical tests such as the ADF unit root test and the modified causality test to observe the causal association among the long-run dependent and independent variables. The results of the study indicate that financial development has various causal relationships with macroeconomic stability in Pakistan. The findings reveal that financial depth, banking sector development, and the size of the equity market have a unidirectional causal relationship with macroeconomic stability, while the saving ratio and control variable inflation have independent causal relationships with the macroeconomic stability of Pakistan. Additionally, the study finds that the saving ratio has a unidirectional causal connection with banking sector development and unidirectional causality with financial deepening. Furthermore, there exists a bidirectional causal association between banking sector development and macroeconomic stability in Pakistan. Our findings suggest the need to accelerate the financial reforms which were initiated by the government in the late 1980s and to improve the efficiency financial systems and governance to stimulate saving/investment and, consequently, long-term economic growth.